Aryl hydrocarbon induction of rat cytochrome P-450d results from increased precursor RNA processing. - Silver, G (1990)
We have previously demonstrated that cytochrome P-450d mRNA accumulation is induced at a posttranscriptional level by 3-methylcholanthrene (MCA) in primary cultures of rat hepatocytes grown in serum-free hormonally defined medium. Using dactinomycin chase experiments in this culture system, we found that MCA had no effect on the P-450d mRNA half-life. In addition, induction of P-450d occurred both in the presence and in the absence of protein synthesis inhibitors. An analysis of nuclear precursors showed that the accumulation of the primary transcript of the P-450d gene was induced to the same extent as that of the mature mRNA after MCA treatment and that the pattern of accumulation of precursors differed between treated and control liver cells. Since P-450d induction is thought to be a receptor-mediated event, these data are consistent with a model in which a direct interaction occurs between the receptor-ligand complex and the primary transcript.